THE FIRST GALAXIES: ASSEMBLY UNDER RADIATIVE FEEDBACK FROM THE FIRST STARS - Pawlik, Andreas H.; Milosavljević, Miloš; Bromm, Volker (The Astrophysical journal, 2013)
We investigate how radiative feedback from the first stars affects the assembly of the first dwarf galaxies. To this end, we perform cosmological zoomed smoothed particle hydrodynamics simulations of a dwarf galaxy assembling inside a halo reaching a virial mass ~10[sup 9] M at z = 10. The simulations follow the non-equilibrium chemistry and cooling of primordial gas and the subsequent conversion of the cool dense gas into massive metal-free stars. To quantify the radiative feedback, we compare a simulation in which stars emit both molecular hydrogen dissociating and hydrogen/helium ionizing radiation with a simulation in which stars emit only molecular hydrogen dissociating radiation, and further with a simulation in which stars remain dark. Our conclusions regarding the structure and observability of the first galaxies are subject to our neglect of feedback from supernovae and chemical enrichment as well as to statistical uncertainties implied by the limited number of galaxies in our simulations.